Hambatan Hukum dalam Penanaman Modal Asing Agribisnis Kehutanan di Provinsi Aceh - Mujibussalim Mujibussalim; Mahfud Mahfud; Sanusi Bintang; Fikri Fikri (Universitas Syiah Kuala, 2014)
The research shows, that regulations which can ve a hurdle in the implementation of foreign investment in Aceh Province namely relating to ... usage in the rule of each article is not well and correct, lack of special the regarding negative investmen in qanun (local law) Aceh concerning Capital Investment, the rule on cooperation with UMKM (small emerprise) for all industries of foreign investment is not corect and complete, the absence of concerning capital investmen of agriculture forestry. Beside the rules on foreign capital investment problems in the sector of agriculture business of is still found in several source and the rule regarding the settlement of is laso not good yet and complete. Legal Hurdles in Foreign Agribusiness Capital Investment in Aceh Province